GOOD CORPORATE GOVERNANCE MECHANISM FOR IMPLEMENTING CORPORATE SOCIAL RESPONSIBILITY IN MINING COMPANIES - Bonar Habib Purba; Haninun; Aminah; Khairudin (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
The purpose of this study is to identify Good Corporate Governance mechanisms that affect Corporate Social Responsibility disclosure. The GCG mechanism is assessed using the Institutional Ownership Measure, Manager Ownership, and the Independent Board of Commissioners. Information is collected through annual reporting of mining business entities for the 2021 period. The total population consists of 90 mining business entities, and 90 samples obtained through a purposive sampling approach. Information is measured through multiple linear regression. The findings of the study show that institutional ownership does not have a major impact on CSR disclosure, management ownership does not have a major impact on CSR, while the independent board of commissioners has a major impact on CSR.